Prototipe Sistem Tiket Layanan Digital Di PLN UP 3 Ampera Palembang - Kadek Arya Puje Arsane; Leon A. Abdillah (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
Digital transformation has become a crucial strategy in improving public service quality across various sectors, including the energy and electricity industry. This article describes the creation of a prototype digital service ticket system at PLN UP 3 Ampera Palembang, which aims to improve the efficiency and accuracy of customer service administration. The current manual procedure frequently resulted in delays, data discrepancies, and issues monitoring service requests. In this regard, PT PLN (Persero) S2JB Ampera Branch in Jakabaring has taken an innovative step by designing and implementing a digital ticketing system. This system was specifically developed to replace the previously manual service process, which was often slow, inefficient, and lacked transparency. Using a prototype development method, the system was built in an iterative manner, involving end users directly during the testing phase. The implementation results demonstrate that the digital ticketing system successfully streamlines customer service workflows, enhances customer satisfaction, and simplifies the tasks of field officers in recording and responding to reports or complaints.